Risk assessment of Xanthomonas citri pv. viticola for the EU. (2nd December 2022) - ; Bragard, Claude; Baptista, Paola; Chatzivassiliou, Elisavet; Di Serio, Francesco; Gonthier, Paolo; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Plant Health performed a risk assessment of Xanthomonas citri pv. viticola (Xcv). This pest causes bacterial canker of grapevine and is reported from Brazil and India. Two scenarios were considered: scenario A0 (current practice) and A2 (additional control measures). For the fresh grape import pathway, scenario A0 results in an order of magnitude of about one entry per 10 years (median; 90% uncertainty interval between ca. one entry per 18, 000 years and ca. five entries per year). For the Vitis spp. plants for planting for research/breeding purposes import pathway, the risk of entry is several orders of magnitude smaller than the risk due to fresh grape import. This outcome is also obtained under scenario A2. The key entry uncertainties include import volume and transfer (for plants for planting), transfer and the disaggregation factor (for fresh grapes) and the limited availability of epidemiological data. The extent of the area favourable for Xcv establishment in the EU is uncertain, illustrating the limitations of climate suitability assessments when based on few data points and little epidemiological information. Nevertheless, the risk of Xcv establishment is only slightly lower than the risk of Xcv entry, i.e. no major establishment constraints are expected for most entries. Similarly, the risk of Xcv establishment is assessed as only slightly lower under current climate compared to the climate of 2041–2060. For grapevine growing areas in the EU with average yearly temperature above 17°C, the lag phase between establishment and spread is expected to be about 3 years (median; 90% range between ca. 6 months and ca. 6 years). Under the same scenario, the rate of spread by natural means is assessed to be ca. 300 m/year (median; 90% range between ca. 35 and ca. 800 m/year). The spread rate would be considerably higher considering movements of plants and cutting tools or machinery. The percentage of grapevine plants infected by Xcv in production sites as yearly average over a 30‐year production cycle is estimated to be ca. 17% (median; 90% range between ca. 1.5% and ca. 46%) in table grapes and ca. 12% (median; 90% range between ca. 0.7% and ca. 37%) in wine grapes. Impacts have been reported to be severe in Brazil and India, but the estimates provided here show that there is considerable uncertainty about expected impacts in the EU.